Pembuatan Autodesk Autocad 2022 Piston Sepeda Motor - Raharjo Raharjo (Jurnal Sains dan Ilmu Terapan, 2024)
Background of the study: The development of mechanical engineering is currently increasing very rapidly. This is especially true for the variation of design programs through computerized systems. One of the programs on the computer in designing images is the AutoCad program. This image design is very important to be applied to mechanical engineering programs, including piston manufacturing. The piston is the core of the working process of an engine in a motor vehicle. The purpose of this study is to Create Autodesk Autocad 2022 Motorcycle Pistons. The research method is qualitative. The findings showed that the Creation of Autodesk Autocad 2022 Motorcycle Pistons consists of several components including (E) Exhaust Camshaf Intake Camshaft, (S) Bosi (V) Valves (valve) (P) Piston Connecting rod, (C) Camshaft rod, (C) Camshaft, (W) water sheath for cooling flow. The implication of this study is that Autodesk Autocad 2022 Motorcycle Pistons in 2023 consist of several interacting components.